Relationship between Parents’ Experience with Giving Complete Basic Immunization to Infants in The Working Area of the Montasik Health Center, Aceh Besar District - Ita Susanti; Nur Asyiah Putri Helnasari; Maharani Maharani (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: The basic immunization program organized by the Government is urgently needed for children aged 0-12 months. One of the reasons for the low coverage of complete basic immunization in the work area of ​​the Montasik Health Center is the past experience of parents and families who have experienced Adverse Events after Immunization, then the next child they refuse to be re-immunized. This is because the parent gets pressure from the family and follows the advice the family more than health workers. Parents mentioned that the Adverse Events after Immunization is that are often experienced by infants include mild to severe fever, the baby has swelling at the injection site and seizures due to high fever after immunization. Methods: This cross-sectional was conducted in the working area of ​​the Montasik Health Center on January, 2022. The population in this study was 178 people consisting of 30 villages, while the sampling technique was cluster random sampling, which was 53 people. Test analysis of research results using the chi-square test. Results: Most of the 12-month-old did not get complete basic immunization, (83.0%), 37 parents who have experience and did not complete basic immunization for their infants (75.7%). Parent’s experience and the provision of complete basic immunization in the work area of ​​the Montasik Health Center Aceh Besar, the value was 0.028 (< 0.05). Conclusion: There is a relationship between parent’s experience with the provision of complete basic immunization in the work area of ​​the Montasik Health Center, Aceh Besar District.